2018
DOI: 10.2147/ppa.s179488
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence during laboratory workup for primary aldosteronism: pilot study

Abstract: PurposeCurrent hypertension guidelines stipulate that all incompatible medications be stopped before performing laboratory screening for aldosteronism, but patient adherence is unclear. We measured plasma drug concentrations to determine drug adherence and potential drug bias during biochemical tests.Patients and methodsPlasma concentrations of 10 antihypertensive drugs were quantified by mass spectrometry in 24 consecutive ambulatory patients with uncontrolled hypertension routinely evaluated for aldosteronis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, the problematic issue is the accurate knowledge about the medications patients are taking. The pilot study by Sandbaumhuter et al illustrates very poor adherence to prescribed therapy as 33% of patients were having plasma drug results different from the preconceived (55). That may lead to mistakes while interpreting ARR in accordance to medications' influence on hormone levels if we do not discuss this matter very carefully with the patient.…”
Section: Diagnostic Work-up For Primary Aldosteronism -Withdraw or Domentioning
confidence: 97%
“…However, the problematic issue is the accurate knowledge about the medications patients are taking. The pilot study by Sandbaumhuter et al illustrates very poor adherence to prescribed therapy as 33% of patients were having plasma drug results different from the preconceived (55). That may lead to mistakes while interpreting ARR in accordance to medications' influence on hormone levels if we do not discuss this matter very carefully with the patient.…”
Section: Diagnostic Work-up For Primary Aldosteronism -Withdraw or Domentioning
confidence: 97%
“…33 Another study found unexpected (unprescribed) use of β-adrenoreceptor and renin-angiotensin-aldosterone system blockers in 25% of hypertensive patients. 34 Those patients may be receiving BP-lowering agents such as beta-blockers or RAS-blockers prescribed for cardiovascular disease protection (or postmyocardial infarction) rather than for BP-lowering per se.…”
Section: Ethical Implicationsmentioning
confidence: 99%
“…Blood is less often used for qualitative analysis in adherence testing [51][52][53] but is more frequently used for quantification. 34,45,[54][55][56][57][58] Certain groups have started quantifying antihypertensive drugs and comparing the results against the established peak (C max ) and minimal/trough (C min ) plasma drug concentrations. 45,54,57,59 These may provide a putative range indicative of regular intake (below steady-state range in Figure 2).…”
Section: Blood Assaysmentioning
confidence: 99%